Randomized clinical trial of the effect of preoperative Dexamethasone with local anaesthetic on postoperative pain after laparoscopic cholecystectomy - Hossain, Moazzem; Hoque, Md. Ariful; Shadia, Shamima Nasrin (Jour Med Resh and Health Sci, 2021)
Laparoscopy is now a common procedure in many surgeries as it contains many advantages. Local anaesthetic drugs have been using for this purpose to reduce post-operative pain.Addition of dexamethasone with local anaesthetic drugs give prolong post operative analgesia.The study was a randomized prospective type of observational study. The study was conducted in the Department of Anesthesiology of Bangladesh Medical College Hospital. Results were presented in table, charts and expressed as percentages/ proportions, mean and average. In present study among the thirty (30) patients 12(40%) were male and 18(60%) female. The number of Diabetic Patient 9 (23%) out of total 30 study population. , hours of first demand of rescue analgesia is significantly higher in 10 th to 12 hours and average 10.75 hours.The scenario of diabetic patient is, they need less analgesia than non-DM patients. The demand of rescue analgesia average 11.50th hour in Diabetic patients. We need planning for postoperative pain management should initiate in the preoperative period.counseling about the degree of pain that should reduce the patient’s anxiety and the fear of unrelieved pain.